Effect of crosslinking on the properties of membrane formulated from quaternized chitosan / N. Z. Kassim Shaari, M. A. N. Kamarulzaman and N. S. I. Chik - Kassim Shaari, N. Z.; Kamarulzaman, M. A. N.; Chik, N. S. I. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Heavy metals are easily absorbed by living things because of their high-water solubility. Adsorption is a popular separation technique that is used to remove heavy metals from water since it is inexpensive, widely available, and ecologically benign. Chitosan's structure includes hydroxyl and amino groups, which make it a popular adsorbent for heavy metals. In this study, quaternization was used to change chitosan and improve its adsorption capacity. As the quaternizing agent, hexadecyltrimethylammonium bromide (TMAB) was employed. After blending the quaternized chitosan with polyvinyl alcohol and polysulfone, a membrane was created, and tetraethyl orthosilicate (TEOS) was used to crosslink it. Tetraethyl orthosilicate loadings of 1, 2, and 4 weight percent were added to the membrane formulation as a crosslinker. The surface morphology and surface charge of the prepared membranes were then described. Antifouling analysis and water permeation were used to test the performances. According to the results, membrane M4 with 4 weight percent TEOS exhibited the best characteristics, especially in terms of surface charge and surface morphology with strong antifouling capabilities. Furthermore, it has the highest water flux attributed to good surface hydrophilicity. The developed membranes may find application in the heavy metal removal phase of water treatment.